Splošni pregled nevrodegenerativnih bolezni - Kočivnik, Nina (Placebo, 2024)
Neurodegenerative diseases are a heterogeneous group of diseases characterised by gradual loss of nerve cells which consequently shows as the degeneration of various parts of the nervous system. The extent of neuronal loss is usually related to the occurrence and progression of disease-specific clinical symptoms. The most common neurodegenerative diseases include Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis and Huntington's disease, which are discussed in detail in this review. Neurodegenerative diseases are permanent and incurable. Although several medications are currently approved for their treatment, most of them only alleviate the symptoms. Therefore, several studies are currently being conducted with the aim to understand mechanisms of these diseases, which could lead to the development of effective therapies for their treatment.
Keywords: Alzheimerjeva bolezen; amiotrofična lateralna skleroza; Huntingtonova bolezen; Nevrodegenerativne bolezni; Parkinsonova bolezen